1995
DOI: 10.1164/ajrccm.152.1.7599824
|View full text |Cite
|
Sign up to set email alerts
|

Sleep stage influences the hemodynamic response to obstructive apneas.

Abstract: Blood pressure (BP) rises at the termination of obstructive episodes in patients with sleep apnea. Although the relationship of these BP elevations to oxygen saturation (SaO2) and arousal has been explored, the influence of sleep stage is undefined. To examine the effects of sleep stage on the postapnea BP elevation, we enrolled 12 patients with obstructive sleep apnea (OSA), and successfully collected data from seven of these (all male). Subjects slept overnight in the sleep laboratory, with full sleep and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…During REMS, the arousal response to hypoxia, hypercapnia, and upper-airway stimulation is attenuated in dogs 2224 . The arousal response to hypoxia, hypercapnia, and upper-airway stimulation is not consistently blunted during REMS in healthy humans 2527 , but obstructive events are more common and oxygen desaturation more severe during REMS in OSA patients 28, 29 . This has been attributed to an increase in arousal threshold during REMS relative to NREMS 30 .…”
Section: Resultsmentioning
confidence: 92%
“…During REMS, the arousal response to hypoxia, hypercapnia, and upper-airway stimulation is attenuated in dogs 2224 . The arousal response to hypoxia, hypercapnia, and upper-airway stimulation is not consistently blunted during REMS in healthy humans 2527 , but obstructive events are more common and oxygen desaturation more severe during REMS in OSA patients 28, 29 . This has been attributed to an increase in arousal threshold during REMS relative to NREMS 30 .…”
Section: Resultsmentioning
confidence: 92%
“…GARPESTAD et al [23] reported that the blood pressure in REM sleep with a 78±82% Sa,O 2 level was significantly higher than that of NREM sleep at the same saturation levels [23]. These investigators also found that, in REM sleep, further desaturation with significant lengthening of obstructive apnoea was accompanied by a significantly higher postapnoeic blood pressure elevation.…”
Section: Discussionmentioning
confidence: 97%
“…In each patient, both before and after treatment, all apnoeic and hypopnoeic events with a BP signal free from artefacts over the whole respiratory event, and the following unoccluded ventilatory interval were considered for BP measurements. Events during which the Finapres device operated servo set-point adjustments that could affect the evaluation of BP swings were excluded; events had to be separated from an REM period by o10 min, as sleep stage may influence BP behaviour during sleep in OSA [20]. The following variables were measured: difference between highest BP after and lowest BP during the event (systolic (DPs) and diastolic (DPd) BP values, respectively), highest Sa,O 2 preceding the event, lowest Sa,O 2 following the event, and difference between these two values (DSa,O 2 ).…”
Section: Methodsmentioning
confidence: 99%